2010
DOI: 10.1007/s00330-010-1764-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of contrast-enhanced magnetic resonance angiography (MRA) using Gd-DOTA compared with time-of-flight MRA in the diagnosis of clinically significant non-coronary arterial disease

Abstract: Contrast-enhanced MRA using Gd-DOTA at 3 T was superior to unenhanced TOF MRA in the vascular territories investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
(24 reference statements)
1
2
0
Order By: Relevance
“…Our results show parallels to the study of Kang et al, who compared 2D TOF and CEMRA for stenosis evaluation of peripheral, renal, and carotid arteries at 3T [14]. Kang et al found CEMRA to have better sensitivity and specificity for carotid artery stenosis than TOF.…”
Section: Discussionsupporting
confidence: 88%
“…Our results show parallels to the study of Kang et al, who compared 2D TOF and CEMRA for stenosis evaluation of peripheral, renal, and carotid arteries at 3T [14]. Kang et al found CEMRA to have better sensitivity and specificity for carotid artery stenosis than TOF.…”
Section: Discussionsupporting
confidence: 88%
“…CE-MRA for the evaluation of atherosclerotic vascular disease is particularly problematic given the high concurrent incidence of renal impairment. Thus, there has been an increased impetus to develop unenhanced MR techniques of comparable accuracy and efficiency to CE-MRA [50]. Numerous studies have shown CE-MRA to be an accurate, reliable diagnostic tool in the evaluation of stenosis degree and also in the measurement of cross-sectional vessel area-an important value to establish before intervention, particularly before stenting or deployment of other vessel prostheses [51].…”
Section: Discussionmentioning
confidence: 99%
“…TOF-MRA is commonly used to assess carotid artery stenosis; however, it is weak to signal-intensity drop-out artifacts in stenotic vascular segments, and suboptimal for the assessment of the great vessel origins (16,17). In particular, long imaging times with TOF-MRA limit anatomic coverage; whereas, TR-CEMRA offers combined anatomic and hemodynamic information rapidly, without a timing run (18).…”
Section: Discussionmentioning
confidence: 99%